New entry proposal in a dictionary: A case study for the entry lotus - Sutami, Hermina; Xinchun, Su; Wiratikusuma, Fransiska (citeus, 2022)
The object of this study is the word lotus. In the Comprehensive Indonesian Dictionary (KBBI), the lotus entry has only one meaning within the botanical domain. However, the word lotus is also present and used in the context of Buddhism in Indonesia. Based on this fact, it is suggested to add a new meaning to the entry. The problem is to decide whether the new meaning is a polysemy or a homonym, and the criteria used to determine this. The purpose of this research is to provide input to the Language Development and Fostering Agency to add new word entries to the KBBI using a case study of the word 'lotus' entry. Our research results on the word 'lotus' can expand the knowledge of the Indonesian people from the domain of botany to the domain of religion. In order to determine whether the entry is a polysemy or a homonym is carried out through Peirce's semiotic theory developed by Ogden and Richards to examine the relationship between three components that make up the word lotus as a sign. The research method involves analyzing the difference between the basic meaning and the new meaning, whether there is a development of a new meaning or a completely different meaning from the basic meaning. Unlike the previous studies, this research views meaning as a sign component. The lotus entry is a sign consisting of symbol, thought or reference, and reference components.